Searching eyes privacy, the state, and disease surveillance in America - Fairchild, Amy L.; Bayer, Ronald; Colgrove, James Keith (Univ. of California Press [u.a.], 2007)
This history of public health service in the United States spans more than a century of conflict and controversy with the authors situating the tension inherent in public health surveilance in a broad social and political context.
Includes bibliographical references (p. 257-327) and index
Preface: the politics of privacy, the politics of surveillance -- Introduction: surveillance and the landscape of privacy in twentieth-century America -- Opening battles: tuberculosis and the foundations of surveillance -- Raising the veil: syphilis and secrecy -- The right to know: detection, reporting, and prevention of occupational disease -- The right to be counted: confronting the "menace of cancer" -- Who shall count the little children? from "crippled kiddies" to birth defects -- AIDS, activism, and the vicissitudes of democratic privacy -- Counting all kids: immunization registries and the privacy of parents and children -- Panoptic visions and stubborn realities in a new era of privacy -- Conclusion: an enduring tension
Keywords: Public health surveillance; Privacy, Right of; Population Surveillance / United States; Confidentiality / United States; Health Policy / history / United States; Privacy / United States; Public Health Practice / history / United States; Confidentiality -- United States; Health Policy -- history -- United States; Population Surveillance -- United States; Privacy -- United States; Public Health Practice -- history -- United States; Meldepflichtige Krankheit; Gesundheitsberichterstattung; Datenerhebung; Datenschutz; USA